TECHNICAL KNOWLEDGE OF CREATING DIGITAL VISUAL CONTENT FOR MODEST FASHION BRANDING: A CASE STUDY OF STUDENT INTERNSHIP AT PT BILQIS BANGUN CITRA - Wasi Safany; Amanda Chandra Maharani; Syarifah Nur Hajja (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
This study discusses branding strategies in the modest fashion industry through digital visual content based on the internship experience of a Batik Fashion Design student from ISI Surakarta at PT Bilqis Bangun Citra. Using a descriptive qualitative approach with a practice-based artistic method, the study shows that the production of visual content such as product catalogs, promotional videos, and live social media broadcasts significantly strengthens brand identity. The student’s involvement enhanced both technical skills and cultural communication within the local fashion industry. Keywords: digital branding, visual content, modest fashion, internship, MBKM